Digitalization of Business and Legal Glossaries: Accelerating Translators Working Performance? - Sukaesih, Ina; Edel, Eky Erlanda; Humolungo, Farizka; Zaman, Mochamad Nuruz (KnE Social Sciences, 2024)
The demand for professional translation services has grown exponentially in an increasingly globalized world. However, translators face numerous challenges in ensuring accuracy, consistency, and efficiency, especially when dealing with specialized fields such as business and legal translation. This mixing method research conducted at the study program in English for Business and Professional Communication (BISPRO) of Politeknik Negeri Jakarta, explores the potential benefits of digitizing business and legal glossaries to enhance translators’ working performance by exploring the advantages of digital technology in the translation of the legal and business documents. The research aims to investigate the challenges and the advantages of digital glossaries, including ease of access, real-time updates, and enhanced search capabilities. It discusses the utilization of technology such as mobile applications. The research findings suggest that digitizing business and legal glossaries has the potential to significantly accelerate translators’ working performance, leading to improved translation quality and efficiency. Furthermore, it also suggests the need for continued innovation in translation technology and the establishment of standardized practices for digital glossary creation and utilization in translation. Keywords: digital glossary, digital tools, translation, for legal, translation for business